Salt-induced and alcohol-induced hydrophobic and underoil superhydrophobic poly (vinylidene fluoride) membranes for effective oil collection. Issue 1 (February 2021) - Song, Hai-Ming; Zhu, Li-Jing; Wang, Gang; Yang, Hao; Zeng, Zhi-Xiang; Wang, Ling-Hui
Graphical abstract: Highlights: A facile PVDF membranes fabrication method. Alcohol-induced and salt-induced NIPS process. Porous membranes for oil-water separation. Abstract: A one-step and facile non-solvent induced phase separation (NIPS) was used to prepare poly (vinylidene fluoride) (PVDF) porous membrane using water, alcohol and saturated salt solution as the non-solvent. Affected by the coagulation, various morphology and crystalline forms were formatted. Strong α-phase and weak β-phase dominated the surface of the water-induced and alcohol-induced PVDF membranes, while new γ-phase and increased β-phase appeared on the saturated salt solution-induced membranes without α-phase. Meanwhile, high roughness and rich micro/nanostructure were obtained, leading to hydrophobic and underoil superhydrophobic surfaces. The as-prepared membranes exhibited excellent oil permeation compared with the commercial membranes, good stability and regeneration, and outstanding antifouling performances. Furthermore, a simple oil recovery bag was fabricated by the fabricated membranes. Floating oil can be absorbed and recovered by the device when put it into the water/oil mixture, which has a wide prospect in oil recovery field.